2015
DOI: 10.1021/acs.nanolett.5b00513
|View full text |Cite
|
Sign up to set email alerts
|

Open-Circuit Voltage Deficit, Radiative Sub-Bandgap States, and Prospects in Quantum Dot Solar Cells

Abstract: Quantum dot photovoltaics (QDPV) offer the potential for low-cost solar cells. To develop strategies for continued improvement in QDPVs, a better understanding of the factors that limit their performance is essential. Here, we study carrier recombination processes that limit the power conversion efficiency of PbS QDPVs. We demonstrate the presence of radiative sub-bandgap states and sub-bandgap state filling in operating devices by using photoluminescence (PL) and electroluminescence (EL) spectroscopy. These s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
245
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(263 citation statements)
references
References 54 publications
(136 reference statements)
17
245
1
Order By: Relevance
“…9À11 Recently, Bawendi et al reported the presence of emissive IGS that form an "effective band" inside the band gap and ∼0.2 eV away from the band edge, which were believed to be at the origin of the high open-circuit voltage deficit in the QD solar cells. 12 Remarkably, this is in good agreement with our previous work, where we found a band of IGS ≈ 0.2 eV above the valence band of PbS QDs, which form percolation pathways assisting carrier transport. 13,14 In addition, Sargent et al and Klimov et al found similar IGS using transient absorption and scanning tunneling spectroscopy (STS) methods.…”
supporting
confidence: 93%
“…9À11 Recently, Bawendi et al reported the presence of emissive IGS that form an "effective band" inside the band gap and ∼0.2 eV away from the band edge, which were believed to be at the origin of the high open-circuit voltage deficit in the QD solar cells. 12 Remarkably, this is in good agreement with our previous work, where we found a band of IGS ≈ 0.2 eV above the valence band of PbS QDs, which form percolation pathways assisting carrier transport. 13,14 In addition, Sargent et al and Klimov et al found similar IGS using transient absorption and scanning tunneling spectroscopy (STS) methods.…”
supporting
confidence: 93%
“…Corroborating this claim, we observe an increased PL from energies lower than the bandgap for ligand exchanged CQDs ( Figure S6, Supporting Information), which, in accordance to several reports in the literature, we explain as trap-induced emission. [4,[19][20][21] Moreover, large CQDs, with their smaller surface to volume ratio and longer reaction time, are considered to exhibit a lower surface trap density, which we observe as a distinctly lower PIA signal for all employed ligands. This effect would not be explained by assuming intraband transitions to be responsible for the absorption bands.…”
Section: Resultsmentioning
confidence: 97%
“…[18] The corruption of a clean bandgap via ligand exchanging was furthermore related to the emergence of photoluminescence (PL) at energies below the direct bandgap transition. [4,[19][20][21] Indeed, these works underlined that these states lead to a significant reduction in open circuit voltage and thereby overall solar cell efficiency. [21,22] A clear understanding of these IGS and how to suppress them is thus crucial for further improvement of these materials for future applications.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most works have focused on the transport in CQD solids [15][16][17] or the photophysics 18 , and only a few have investigated the working mechanisms of CQD solar cells in detail 14,19,20 . In this letter, we use timedelayed collection field (TDCF) 21 , bias-assisted charge extraction (BACE) 22 and steady state measurements to investigate free charge generation and recombination in PbS CQDs Schottky structure solar cells.…”
mentioning
confidence: 99%